2017
DOI: 10.18632/oncotarget.18462
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin I2 is responsible for ameliorating prostaglandin E2 stress in stimulating the expression of tumor necrosis factor α in a β-amyloid protein -dependent mechanism

Abstract: Cyclooxygenase-2 (COX-2) has been found to be induced during the early stage of Alzheimer’s disease (AD). Using mouse-derived astrocyte and APP/PS1 transgenic (Tg) mice as model systems, we firstly elucidated the mechanisms underlying COX-2 metabolic production including prostaglandin (PG)E2- and PGI2-mediated tumor necrosis factor α (TNF-α) regulation. Specifically, PGE2 accumulation in astrocyte activated the p38 and JNK/c-Jun signaling pathways via phosphorylation, resulting in TNF-α expression. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…The roles of PGI 2 in AD are complicated. PGI 2 treatment suppressed Ab production via inhibition of the p38 and JNK/c-Jun in APP/PS1 Tg mice (63). PGI 2 stimulated tau phosphorylation in Tau P301S Tg mice (64).…”
Section: Signaling Pathways Involved In Mediating the Effects Of Cox-...mentioning
confidence: 99%
“…The roles of PGI 2 in AD are complicated. PGI 2 treatment suppressed Ab production via inhibition of the p38 and JNK/c-Jun in APP/PS1 Tg mice (63). PGI 2 stimulated tau phosphorylation in Tau P301S Tg mice (64).…”
Section: Signaling Pathways Involved In Mediating the Effects Of Cox-...mentioning
confidence: 99%
“…On the other hand, it was reported that PGI 2 counteracts PGE 2 -induced IFN-g production levels in mouse brain in an Ab-dependent mechanism (Wang et al, 2016b). Interestingly, another group also demonstrated that PGI 2 ameliorated the exacerbating effect of PGE 2 on cognitive disorder in APPS/PS1 mice (Zheng et al, 2017). Overall, the studies investigating the role of IP and EP receptors in AD are mostly restricted to animal models, thus further studies are warranted to examine whether and how PGI 2 and PGE 2 are involved in the development and/or treatment of AD in humans.…”
Section: A Central Nervous Systemmentioning
confidence: 99%
“…The upregulation of cyclooxygenase-2 (COX-2) and prostaglandins (PGs) contribute to the pathogenesis of AD, particularly through PGE2 and PGI2, by inducing Aβ production and triggering hyperphosphorylation of tau protein [ 148 ]. DP1, a prostaglandin receptor, is overexpressed in astrocytes and microglia in amyloid plaques in both AD patients and Tg2576 mice [ 149 ].…”
Section: Astrocytes As a Therapeutic Target: Treatment And Neuroprote...mentioning
confidence: 99%